2015
DOI: 10.1038/srep12713
|View full text |Cite
|
Sign up to set email alerts
|

The impact of osteopontin on prognosis and clinicopathology of colorectal cancer patients: a systematic meta-analysis

Abstract: Colorectal cancer (CRC) is one of the most frequent malignant neoplasms worldwide. Up to now, no biomarker has been used to predict the prognosis and surveillance of patients with CRC. Recently, the association between osteopontin (OPN) overexpression and the prognosis of CRC was investigated widely, but the results were inconsistent. Therefore, the aim of present meta-analysis was to assess the prognostic effect of osteopontin in patients with CRC. PubMed, EMBASE, Web of Science, Scopus and Chinese Medical Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
2
37
2
1
Order By: Relevance
“…OPN is another key inflammatory cytokine with functional diversity regulating inflammation, chemotaxis and angiogenesis. OPN is upregulated in several malignancies and is associated with poor outcome and, overexpression of OPN in breast cancer may be associated with poor overall survival (163)(164)(165)(166)(167).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OPN is another key inflammatory cytokine with functional diversity regulating inflammation, chemotaxis and angiogenesis. OPN is upregulated in several malignancies and is associated with poor outcome and, overexpression of OPN in breast cancer may be associated with poor overall survival (163)(164)(165)(166)(167).…”
Section: Resultsmentioning
confidence: 99%
“…Emerging data also support OPN as a key mediator in epithelial-mesenchymal transition necessary for cancer progression and metastasis through the stimulation of CAFs and the secretion of transforming growth factor and IL-6 (161,162). Several meta-analyses in different malignancies such as colorectal, breast, lung, prostate cancer and studies of melanoma and glioblastoma have shown reduced overall survival for patients with high levels of OPN in plasma or serum, or increased expression in tumor tissue (163)(164)(165)(166)(167). Phytoestrogens may influence OPN secretion and in preclinical studies of prostate cancer, GEN has shown a biphasic dose-dependent effect on OPN expression and OPNmediated tumor growth and survival (168,169).…”
Section: Osteopontinmentioning
confidence: 95%
“…Numerous studies have revealed the roles that OPN plays in tumour biology, participating in inflammation, tumour progression and metastasis . Recent studies have demonstrated overexpression of OPN in many human carcinomas, including lung, breast and gastric cancer, hepatocellular carcinoma and colorectal cancer . Notably, OPN appears to play a main role in the mechanisms deployed by tumours to evade immune recognition by participating in the crosstalk between cancer cells and the host microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent studies have demonstrated overexpression of OPN in many human carcinomas, including lung, breast and gastric cancer, hepatocellular carcinoma and colorectal cancer. 51 Notably, OPN appears to play a main role in the mechanisms deployed by tumours to evade immune recognition by participating in the crosstalk between cancer cells and the host microenvironment. Furthermore, the human OPN transcript is subject to alternative splicing, and the expression patterns of splicing factors dictate the major OPN splicing isoform in a specific pathological condition.…”
Section: Discussionmentioning
confidence: 99%
“…that OPN expression was inversely correlated with prognosis in AML patients (11,12,14). Whereas the majority of the publications had focused on solid tumors (18)(19)(20)(21), there have been recent studies on the role of OPN in hematological malignancies (10,12). Increased serum OPN concentrations have been reported in chronic myeloid leukemia, multiple myeloma and AML (22).…”
Section: Discussionmentioning
confidence: 99%